Can phenotypic rescue from harvest refuges buffer wild sheep from selective hunting?. Issue 17 (14th August 2014) - Pelletier, Fanie; Festa‐Bianchet, Marco; Jorgenson, Jon T.; Feder, Chiarastella; Hubbs, Anne
Abstract Human harvests can unwittingly drive evolution on morphology and life history, and these selective effects may be detrimental to the management of natural resources. Although theory suggests that harvest refuges, as sources of unselected animals, could buffer the effects of human exploitation on wild populations, few studies have assessed their efficiency. We analyzed records from >7000 trophy bighorn rams (Ovis canadensis) harvested in Alberta, Canada, between 1974 and 2011 to investigate if the movement of rams from refuges toward harvested areas reduced the effects of selective harvesting on horn size through phenotypic rescue. Rams taken near refuges had horns on average about 3% longer than rams shot far from refuges and were slightly older, suggesting migration from refuges into hunted areas. Rams from areas adjacent to and far from harvest refuges, however, showed similar declines in horn length and increases in age at harvest over time, indicating a decreasing rate of horn growth. Our study suggests that the influx of rams from refuges is not sufficient to mitigate the selective effects of sheep trophy harvest. Instead, we suggest that selective hunting of highly mobile animals may affect the genetic structure of populations that spend part of the year inside protected areas.